Morphoanatomical study of Matricaria L. (Asteraceae) in Turkey - Huseyin Inceer; Murat Bal (Botanica Serbica, 2019)
In the Turkish flora, the genus Matricaria is present with four taxa, namely M. aurea, M. chamomilla var. chamomilla, M. chamomilla var. recutita and M. matricarioides. This study presents an evaluation of selected diagnostic characters and anatomical traits of the achene (cypsela) of Matricaria in Turkey using univariate analysis (one-way analysis of variance) and multivariate analysis (cluster analysis, principal component analysis) to obtain new information. Three groups are found within the genus Matricaria based on morphoanatomical characteristics. The colour of disc florets, that of ribs on the achenes, the presence or absence of a slime envelope and pericarp thickness are useful for delimitation of Matricaria taxa, and a key to taxa based on these characters together with other diagnostic traits is provided.